Challenges facing trade union on achieving workplace democracy: A case of A to Z textile mill, Tanzania - Pachi, Ramadhan (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial fulfillment of the requirements for the award of Master of Science in Human Resource Management (MSc HRM) of Mzumbe University.